2013
DOI: 10.1007/s10517-013-2086-4
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Genotyping of Helicobacter pylori Gene vacA in Children with Gastroduodenal Diseases and in Adults with Gastric Cancer in Vladivostok

Abstract: Geographical distribution of individual genotypes of Helicobacter pylori, predominance of virulent types in various regions of Russia, particularly in the Prymorye Territory, remains unclear. We examined 115 children with various gastroduodenal pathology and 33 patients with gastric cancer, of which 57.39 and 60% respectively were infected with H. pylori. All samples positive for H. pylori were further analyzed for gene vacA mosaicism. In all clinical subgroups, variants s1 and m1 predominated; the frequency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The cross‐sectional studies on H. pylori infection in symptomatic children as detected by histology are summarized in Figure [references: ] . H. pylori prevalence estimates vary greatly (3%‐76%) with an overall random‐effects regression model estimate of 39% (95% CI: 35%‐43%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cross‐sectional studies on H. pylori infection in symptomatic children as detected by histology are summarized in Figure [references: ] . H. pylori prevalence estimates vary greatly (3%‐76%) with an overall random‐effects regression model estimate of 39% (95% CI: 35%‐43%).…”
Section: Resultsmentioning
confidence: 99%
“…Among children with gastrointestinal symptoms, rates varied from 7% to 76%, with a cluster of studies, 16/43 (37%), reporting prevalence estimates of 30%‐40%. Three studies in children with gastritis or duodenitis reported a 44% positivity rate in Mexico, 46% in Russia and 20% in China . One study in Europe looked at infection rates in children with gastric or duodenal ulcers, in children <6 years old 13% were infected, in 6‐11‐year‐olds 35% and in 12‐18‐year‐olds 38% were infected .…”
Section: Resultsmentioning
confidence: 99%